Independent directors attributes and related party transactions in Malaysia: evidence from an individual perspective - Abd Majid N.; Rahmat M.M.; Ahmed K. (Emerald Publishing, 2024)
Purpose: This study aims to examine the ability of independent directors to discipline related-party transactions (RPTs) among listed companies in Malaysia. Firms typically appoint independent directors individually, not as a group. However, board members are commonly viewed collectively as a group, and evidence of the abilities of individual directors is scarce. Design/methodology/approach: The attributes of individual independent directors include accounting literacy, length of service, audit committee membership and active participation in board and audit committee meetings. The unit of analysis is the individual independent director. The final sample consists of 1,552 observations in 2017, and RPTs are categorized as either efficient or conflicting. Findings: The study finds that the tenure of individual independent directors and active participation in board meetings affect the firms engagement in RPTs. However, the financial literacy, audit committee membership and attendance of independent directors at audit committee meetings do not affect the firms engagement in RPTs, either efficient or conflicting. Overall, this result offers limited support for the upper-echelon theory concerning the attributes of individual independent directors and RPTs. Research limitations/implications: This study uses cross-sectional observations for 2017, which predates the COVID-19 pandemic. Thus, this study ignores the impact of restrictions in community mobility during the pandemic on the independent directors ability to monitor the corporation. This circumstance may have implications for practice and merit further research. Practical implications: The findings provide information for board nominating committees, regulators and policymakers that the capability of individual independent directors to fulfill their responsibilities is limited. The firms nominating committee must be very selective in nominating and appointing independent directors with appropriate competencies. Investors should choose companies that have reappointed the same independent directors for an extended period, as they may benefit from the experience in protecting investors interests. Originality/value: This paper contributes novel evidence to upper-echelon theory literature on the association between independent directors and RPT types from the perspective of individual independent directors. 2023, Emerald Publishing Limited.